A Study of the Conceptual Metaphor in the History of Jahangosha Jovini - Kahkha, Abdolali Oveisi; Teymouri, Ali (Funūn-i adabī, 2022)
Before the advent of linguistics, metaphor was considered only a feature of literary language, especially poetry, which had little to do with other linguistic forms. But cognitive studies of metaphor have changed this traditional view. In this research, after introducing the cognitive approach to metaphor, a conceptual metaphor in the History of Jahangosha is examined. There are many conceptual metaphors in the History of Jahangosha Jovini including concepts of agree, calamity, annihilation, negligence, doubt, luck and happiness, religion, guidance, and forgiveness which are manifested with the target areas of egg, whip, sword, sleep, fire, darkness, Homa, candle, light, and skirt. In these metaphors, Jovini has used almost identical mapping between two domains of organ and purpose. The reason for this is the conditions prevailing in the author’s time. Jovini also used the four elements of water, soil, wind, and fire in materializing abstract concepts. The reason for this can be considered the Mongol invasion because the Mongol invasion brought nothing but destruction. One of the new theories in cognitive linguistics is the concept of ‘conceptual metaphor’. In this theory, linguistic knowledge is not separate from thinking and cognition. According to cognitive linguists, meaning is based on conventional conceptual constructions. In this way, semantic constructions, like other cognitive domains, reflect the mental categories that human beings have shaped through their experiences. In Likoff and Johnson's research, it has been emphasized that metaphor is a fundamental element in our categorization of the outside world and our thought processes” (as cited in Safavi, 2013, p. 367). By applying this theory, one can measure the metaphorical mentality and attitude of a person about various matters, and by examining the various concepts that are conceptualized with a central mapping, one can find out his intellectual and metaphorical system. “Scientists believe that man subconsciously seeks to find commonalities in heterogeneous subjects in order to understand things on the basis of these commonalities” (ibid., p. 325). The processes of human thought are largely metaphorical. This is what is meant when it is said that the conceptual system of man is metaphorically organized and defined in metaphorical language. Metaphors appear precisely in the form of linguistic expressions that are present in the human conceptual system (Likoff & Johnson, 2020, p. 12). The cognitive linguistic perspective believes that metaphorical concepts are based on a variety of human experiences, including correlation in experience, different types of non-objective similarities, common biological and cultural roots, and possibly many others. Metaphors have implications that reveal or highlight them and integrate certain aspects of our experiences. A metaphor may be the only possible way to reveal and coherently organize aspects of our experiences. Metaphors may create realities for us, especially social realities. So, metaphors can be a guide for our next actions. Instead, actions increase the power of metaphors to consolidate our experiences. From this perspective, metaphors can be predictors who realize themselves (Likaf & Johnson, 2017, p. 259). In this research, the author intends to examine the conceptual metaphors in the History of Jahangisha. The concepts that are included in the form of metaphorical definitions are those that correspond to the natural forms of experience. Issues such as love, time, attitude, understanding, discussion, work, happiness, health, dominance, status, and moral principles are natural forms of experience in culture. These are concepts that need to be defined metaphorically because our daily practices are not clear enough. Every culture must provide a more or less successful way of interacting with its environment in order to be able to accept and change that environment. In addition, every culture must define social reality in which people have roles that are meaningful to them and through which they can function socially. Social reality, defined by culture, affects the kind of perception of material reality. Much of our social reality can be understood in metaphorical terms. Therefore, it can be said that metaphor is basically a social necessity. Metaphor is not formed in the mind of an individual alone but is the nature of a collective metaphor. After it is necessarily formed in the society, it is expressed due to the need of the speaker for this kind of discipline, and the purpose of its application is to create a special space in the mind of the listener. An atmosphere that has very strong cognitive and emotional aspects can bring the listener's mind closer to the speaker's mind and create a common ground. In this case, it can be said that the use of metaphors goes beyond the scope of an immediate need and its purpose is to open a way to the themes that the metaphorist seeks to convey to the listener. Therefore, making the concepts that are in the heart of life tangible is one of the main necessities in any society, because by metaphorically defining the concepts, they can be made from abstract to objective and tangible and provide the way for the realization of these concepts. In theHistoryof Jahangisha Jovini, there are many conceptual metaphors, including concepts, calamity, annihilation, negligence, doubt, luck and fortune, religion, guidance, and forgiveness, which are manifested in the target areas of egg, whip, sword, sleep, fire, darkness, Homa, candle, light, and skirt. In these metaphors, Jovini has used almost identical mapping between the two domains of origin and purpose, and the reason for this is the conditions prevailing in the author's time.